Cabanagem and the construction of the amazonian identity: effects of modernity in the context of the cabano people (Research, Society and Development, 2020)
The purpose of this article is to discuss about Cabanagem and the construction of the Amazonian identity related to the effects of modernity in the current context of the Cabana people. Methodologically, the article results from a bibliographical research and discussions during the obligatory discipline of epistemology, from the master's course in anthropic studies in the Amazon. The constructed text demonstrates that identity was based on hatred of white and Portuguese mandonism and the struggle for rights and freedoms. Diverging from this context, Cabanagem was usually, and still is, analyzed as another regional movement, typical of the regency period of the Brazilian Empire. However, the cabanos and their leaders viewed other political and social perspectives. They called themselves hut patriots, creating a sense of identity with diverse ethnicities and cultures. However, it is observed that even if taken in some way by a conscience and decolonial characteristics, one experiences in the present, whether subtly or not, the permanence of colonial influences in the Amazonian life.